Docetaxel-loaded Bovine Serum Albumin Nanoparticles Conjugated Docosahexaenoic Acid for Inhibiting Lung Cancer Metastasis to Bone - Zu, Yuangang; Hu, Yan; Yu, Xueying; Jiang, Shougang (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: Cancer is one of the severest diseases in the world, and lung cancer is one of the five common cancers causing thousands of deaths every year. Moreover, most of the lung cancer patients die because of bone metastasis. Methods: This research was conducted with the aim of developing novel nanoparticles (NPs) of docetaxel (DTX) loaded bovine serum albumin (BSA) conjugated docosahexaenoic acid (DHA) using an emulsion/solvent evaporation method for inhibiting lung cancer metastasis to bone. The in vitro drug release of the DTX-DHA-BSA-NPs showed that the nanoparticles released in a sustained and controlled manner contributed to continual fight against cancer cells. The study results revealed that the DTX-DHA-BSA-NPs had higher antitumor efficacy in comparison with the DTXBSA- NPs or DTX in vitro. Result: The study results also showed that the DTX-DHA-BSA-NPs had higher inhibiting efficacy of lung cancer metastasis to bone in comparison with the DTX-BSA-NPs or DTX in vivo. Furthermore, the mean survival time was longer with DTX-DHA-BSA-NPs (24.40 d) than that of DTX (20.95 d). In consideration of these results, the DTXDHA- BSA-NPs may hold potential for bone metastasis of lung cancer treatment.
Keywords: docosahexaenoic acid